2010
DOI: 10.1186/1476-9255-7-55
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of circulating Annexin A5 in Familial Mediterranean fever

Abstract: BackgroundFamilial Mediterranean fever is a genetic autoinflammatory disease most commonly affecting the ethnic groups originating from around the Mediterranean Sea. Apoptosis plays an important role in down-regulation of the inflammatory response by reducing the lifespan of activated immunocompetent cells. Thus, increased apoptosis may be associated with pathogenesis of familial Mediterranean fever.MethodsIn the present study we determined the serum levels of apoptotic marker, Annexin A5, in familial Mediterr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For locally advanced rectal cancer, an increased mRNA expression of AnxA5, but not AnxA4 was found in tumor tissue after radiochemotherapy [121]. Elevated serum AnxA5 level have been found under inflammatory conditions that are associated with higher IL-1 beta concentrations [122] and it will be of interest to elucidate whether tumor cells can secrete AnxA5 during therapy and thereby mediate their recognition by DCs and subsequent killing via CTLs. The modulation of inflammation and immunity by dying cells and the influence of the PS ligand AnxA5 has been considered in more detail elsewhere [112,123].…”
Section: Interference With Tumor Cell Clearance -Blocking Of Ps With mentioning
confidence: 98%
“…For locally advanced rectal cancer, an increased mRNA expression of AnxA5, but not AnxA4 was found in tumor tissue after radiochemotherapy [121]. Elevated serum AnxA5 level have been found under inflammatory conditions that are associated with higher IL-1 beta concentrations [122] and it will be of interest to elucidate whether tumor cells can secrete AnxA5 during therapy and thereby mediate their recognition by DCs and subsequent killing via CTLs. The modulation of inflammation and immunity by dying cells and the influence of the PS ligand AnxA5 has been considered in more detail elsewhere [112,123].…”
Section: Interference With Tumor Cell Clearance -Blocking Of Ps With mentioning
confidence: 98%
“…In contrast, an endogenous concentration of annexin V in BAL fluid obtained on day 15 was much lower and similarly detectable among treatment groups at 61-143 pg/ml (determined by ELISA, data not shown). Annexin V is an intracellular protein and its serum concentration was reported to range between 1.8 and 2.5 ng/ml in healthy subjects and 5.7 and 11 ng/ml in subjects with various diseases (4,23,36). No data is currently available about endogenous level of annexin V in human COPD.…”
Section: Inhibition Of Efferocytosis By Annexin Vmentioning
confidence: 98%
“…Furthermore, mutant annexin V, which lost binding affinity to PS, did not affect macrophage efferocytosis (19), clearly showing that an inhibitory effect of annexin V was PS-mediated. Notably, an inhibitory effect of annexin V on efferocytosis was concentration-dependent and a relatively higher concentration was needed to exert the effect in these studies, compared with a concentration present in human serum (4,23,36). The extracellular concentration of endogenous annexin V is presumably too low to affect macrophage efferocytosis.…”
mentioning
confidence: 95%
“…6,10 Moreover, animal studies demonstrated diminished macrophages apoptosis in pyrin-truncation mice through an IL-1 independent pathway. 11,12 These results may reflect impaired apoptosis regulation in FMF-patients. However, there are some reports which do not support these results; Gomucio et al found that there is no difference between the effect of wild-type pyrin and mutated pyrin regarding both interaction with the ASC protein and effect on cell death.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies reported that colchicine which could be inhibited apoptosis add to anti-inflammatory effect, reduced the surface expression of Fas. 12,15,16 However, there is no sufficient data about the effect of colchicine on apoptosis in the FMF patients. Boyajyan et al demonstrated less circulating annexin A5 levels which are an apoptotic marker in using regular colchicine patients.…”
Section: Discussionmentioning
confidence: 99%